1997
DOI: 10.1155/mbd.1997.207
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of the Antitumor Agent Vanadocene Dichloride in Physiological and Therapeutic Media, Blood Plasma and Human Blood ‐ An EPR Study

Abstract: By means of EPR spectroscopy the behaviour of the vanadocene dichloride (I), Cp2VCl2 (Cp=η5-C5H5), in various deoxygenated and non-deoxygenated physiological media and therapeutic solution as well as in blood plasma and stabilized human blood was studied. On the basis of measured values of isotropic spectroscopic splitting factor giso and isotropic hyperfine coupling constant Aiso, the vanadocene species, [Cp2V(H2O)Cl]+ (II; giso= 1.985, |Aiso| = 7.68 mT), [Cp2V(H2O)2]2+ (III; giso= 1.983, |Aiso| = 7.92 mT), [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…11 Carbonates seem to be components that are present in all these media and they are able to interact with the vanadocene moiety. It was found that complex 1 introduced into the solution of carbonates at physiological pH gave one simple eight-line EPR spectrum with magnetic parameters corresponding to compound 2 (jA iso 51 V j D 175.1 MHz, g iso D 1.9861).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Carbonates seem to be components that are present in all these media and they are able to interact with the vanadocene moiety. It was found that complex 1 introduced into the solution of carbonates at physiological pH gave one simple eight-line EPR spectrum with magnetic parameters corresponding to compound 2 (jA iso 51 V j D 175.1 MHz, g iso D 1.9861).…”
Section: Resultsmentioning
confidence: 99%
“…11 Bidentate bonded carbonate ligand stabilizes the complex due to chelate effect. So the vanadocene fragment is resistant to degradation at physiological pH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Kopf-Maier andKopf, 1987, 1988;Kopf-Maier, 1993). At present, the potential biomedical applications of these vanadocene diacido complexes are limited because of their variable dissociation, aquation, and subsequent hydrolysis in aqueous media (Toney and Marks, 1985;Vinklarek et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…An EPR spectroscopy was appeared as very efficient method for investigation of such paramagnetic d 1 -complexes. This method should be used at concentration range that is used in biological experiments [13].…”
Section: Introductionmentioning
confidence: 99%